Combination of Co2+-immobilized covalent triazine framework and TiO2 by covalent bonds to enhance photoreduction of CO2 to CO with H2O. Issue 49 (July 2021) - Xu, Ze; Cui, Yao; Young, David J.; Wang, Jixian; Li, Hai-Yan; Bian, Guo-Qing; Li, Hong-Xi
Graphical abstract: Highlights: TiO2 @CTF-Py is combined by a CTF and TiO2 nanoparticles by covalent bonds. TiO2 @CTF-Py exhibits high catalytic activity for the photoreduction of CO2 to CO. Covalent connection and NNN pincer group affect the catalytic activities. Abstract: Pyridine CTF (CTF-Py) grafted on the surface of NH2 -functionalized TiO2 (NH2 -TiO2 ) nanoparticles gave composite TiO2 @CTF-Py covalently linking the inorganic semiconductor to the nitrogen-rich porous, conjugated and coordinating organic functionality. Co 2+ -modified TiO2 @CTF-Py was an efficient photocatalyst for the reduction of CO2 to CO with high selectivity using water as the electron donor and without exogenous photosensitizers or a sacrificial agent. The covalent connection between the semiconductors and NNN coordination group were important for this photocatalytic activity and selectivity.